2011
DOI: 10.1021/ic202255w
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity and Luminescence in Coordination Polymers Based on Copper(I)-Halides and Sulfur-Pyrimidine Ligands

Abstract: The solvothermal reactions between pyrimidinedisulfide (pym(2)S(2)) and CuI or CuBr(2) in CH(2)Cl(2):CH(3)CN lead to the formation of [Cu(11)I(7)(pymS)(4)](n) (pymSH = pyrimidine-2(1H)-thione) (1) and the dimer [Cu(II)(μ-Br)(Br)L](2) (L = 2-(pyrimidin-2-ylamino)-1,3-thiazole-4-carbaldehyde) (2). In the later reaction, there is an in situ S-S, S-C(sp(2)), and C(sp(2))-N multiple bond cleavage of the pyrimidinedisulfide resulting in the formation of 2-(pyrimidin-2-ylamino)-1,3-thiazole-4-carbaldehyde. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 62 publications
5
47
0
Order By: Relevance
“…The Cl3-Cu3-S1, 127.48(10)°; Cl3-Cu3-Cl3C, 121.80(12)°; S1-Cu3-Cl3C, 110.59(9)°, indicating a distorted trigonal geometry. In 1, the Cu-S, Cu-Cl and Cu-N bond lengths are basically consistent with that in other complexes [27][28][29][30][31].…”
Section: [Cu 3 CL 3 (Hmtz)] N (1)supporting
confidence: 83%
“…The Cl3-Cu3-S1, 127.48(10)°; Cl3-Cu3-Cl3C, 121.80(12)°; S1-Cu3-Cl3C, 110.59(9)°, indicating a distorted trigonal geometry. In 1, the Cu-S, Cu-Cl and Cu-N bond lengths are basically consistent with that in other complexes [27][28][29][30][31].…”
Section: [Cu 3 CL 3 (Hmtz)] N (1)supporting
confidence: 83%
“…In the present study, we show that the presence of a thin CuI layer onto the ITO allows controlling the morphology of the polymer films. It has been already shown that CuI and other copper halides can interact easily with organic molecules [46][47][48][49]. For instance, complex formation between CuI and organic molecules leads to different π stacking copper halide motifs [46].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is well-established that the pymSH/pymS − and bis (2-pyrimidyl)disulfide (pym2S2) ligands are good coordinating ligands toward soft Lewis acids such as Cu (I) and it as been shown that, the solvothermal reactions between pyrimidinedisulfide (pym2S2) and CuI in CH 2 Cl 2 :CH 3 CN lead to the formation of [Cu11I7(pymS)4]n (pymSH = pyrimidine-2(1H)-thione) [47]. Another example is presented in [48] where it is shown that solution reaction of CuI and the ligand L((3-bpfob) [L: 1,3-bis(nicotinoyl) o-phenylenediamine] led to the formation of a novel coordination polymer [CuI(3-bpfob)]n that exhibited an unusual one-dimensional helical structure. All these examples show that the CuI exhibits a high tendency to react with an atom donor of organic molecules (as nitrogen, sulphur and oxygen …”
Section: Discussionmentioning
confidence: 99%
“…They are subject to a range of reaction parameters including metal salts, solvent, temperature, and even reaction time. Compared to ambient solution reactions, hydro(solvo)thermal conditions can lead to complicated reactions of heterocyclic disulfides involving intricate rearrangements concurrent with multiple bond cleavage, sometimes resulting in totally unexpected products [20,21].…”
Section: Introductionmentioning
confidence: 99%